A SWOT Analysis of the Greek Health System - Kanellopoulos, Dimitrios (Richtmann Publishing, 2012)
This paper intents to make a SWOT analysis of the Greek health care system. SWOT analysis is a key component in thestrategic planning of the Greek health system. Scope of this analysis is to evaluate the impact of internal and external factors on theGreek health care system. Internal processes and recourses are considered strengths and weaknesses and external factors areconsidered opportunities and threats. By using this analysis we will evaluate the current status of the Greek NHS (national healthcaresystem) and we will identify future prospects.